Planz to put our digital information in its place - Jones, William; Hou, Dawei; Sethanandha, Bhuricha Deen; Bi, Sheng; Gemmell, Jim (Conference on Human Factors in Computing Systems, 2010)
Planz provides a single, integrative document-like overlay to a folder hierarchy through the dynamic, on-demand assembly of XML fragments. This overlay provides a context in which to create or reference not only files but also email messages, web pages and informal notes. This paper describes an evaluation of Planz over a period of several days during which participants compared their experiences on two projects - one involving "status quo" methods, a second project involving Planz. Also discussed is an architecture that extends on the front-end to provide additional overlays and on the back-end in support of additional information stores. Work on Planz is guided by a vision of "structural integrity": Many tools, many modes of interaction applied to a common structure for the organization of and access to personal information.
alt.chi session